Thermal and Electro-thermal System Simulation 2020 - Rencz, Márta; Codecasa, Lorenzo; Poppe, Andras (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book, edited by Prof. Marta Rencz and Prof Andras Poppe, Budapest University of Technology and Economics, and by Prof. Lorenzo Codecasa, Politecnico di Milano, collects fourteen papers carefully selected for the "thermal and electro-thermal system simulation" Special Issue of Energies. These contributions present the latest results in a currently very "hot" topic in electronics: the thermal and electro-thermal simulation of electronic components and systems. Several papers here proposed have turned out to be extended versions of papers presented at THERMINIC 2019, which was one of the 2019 stages of choice for presenting outstanding contributions on thermal and electro-thermal simulation of electronic systems. The papers proposed to the thermal community in this book deal with modeling and simulation of state-of-the-art applications which are highly critical from the thermal point of view, and around which there is great research activity in both industry and academia. In particular, contributions are proposed on the multi-physics simulation of families of electronic packages, multi-physics advanced modeling in power electronics, multiphysics modeling and simulation of LEDs, batteries and other micro and nano-structures.